Integrasi Budaya Lokal dan Program Pelayanan Kesehatan dalam Penanganan Stunting di Wilayah Kerja Puskesmas Maiwa Kabupaten Enrekang - Arman Arman; Nurmiati Muchlis; Nilam Sahratun Nadira; Suharni A. Fachrin; Reza Aril Ahri; Sitti Patimah (FORIKES, 2021)
Stunting is one of the impacts of maternal and child health problems in the long term. Health service programs have not in synergy with the customary patterns and culture of the local community can be an inhibiting factor for the success of the program. The number of stunting cases in South Sulawesi is still quite high. Enrekang Regency is one of the districts with the highest stunting cases. This study aims to analyze the integration of local culture and maternal and child health services in the efforts to deal with stunting in the working area of the Maiwa Health Center. The research design had included qualitative research with a case study approach. The informants in this study were maternal and child health service officers (doctors, nurses, and midwives) including mothers who had children under five years of age and health cadres with the key informant being the head of the Puskesmas. The research location was carried out in the working area of the Maiwa Public Health Center, Enrekang Regency. The results showed that there were efforts to integrate local culture with health service efforts in the form of innovative programs in the community. The existing innovation program has to involve target community groups and health workers including from the private sector. It was hoped that the government, especially the health office as the leading sector, can explore the local potential in each region by involving the local community as the subject, not only as the object of the program. Keywords: local culture; stunting; health service; integration ABSTRAK Stunting merupakan salah satu dampak dari masalah Kesehatan Ibu dan Anak dalam waktu jangka panjang. Program pelayanan Kesehatan yang kurang bersinergis dengan pola kebiasaan maupun budaya masyarakat setempat dapat menjadi faktor penghambat dari keberhasilan program. Jumlah kasus stunting di Sulawesi Selatan dapat dikategorikan masih cukup tinggi. Kabupaten Enrekang merupakan salah satu kabupaten yang menempati kasus stunting tertinggi di Sulawesi Selatan tahun 2018. Penelitian ini bertujuan untuk menganalisis integrasi budaya lokal dan pelayanan kesehatan Ibu dan Anak dalam upaya penanganan stunting di wilayah kerja Puskesmas Maiwa. Desain penelitian termasuk penelitian kualitatif dengan pendekatan studi kasus. Informan dalam penelitian ini adalah petugas pelayanan kesehatan Ibu dan Anak (dokter, perawat, dan bidan) termasuk Ibu yang memiliki Balita Stunting dan kader Kesehatan dengan informan kunci yaitu kepala Puskesmas. Lokasi penelitian dilaksanakan di wilayah kerja Puskesmas Maiwa Kabupaten Enrekang. Hasil penelitian menunjukkan adanya upaya integrasi budaya lokal dengan upaya pelayanan Kesehatan dalam bentuk program inovatif di masyarakat. Program inovasi yang ada melibatkan kelompok masyarakat target dan petugas Kesehatan termasuk dari pihak swasta. Diharapkan kepada pihak pemerintah, khususnya dinas Kesehatan sebagai leading sektor dapat lebih menggali potensi lokal yang ada di masing-masing daerah dengan melibatkan masyarakat setempat sebagai subjek bukan hanya sebagai objek program. Kata kunci: budaya lokal; stunting; pelayanan kesehatan; integrasi